Impacts of common staff on indicators of sanitary evacuation: experience of the gynecology service of Treichville Teaching Hospital - Anongba, Simplice; Dia, Jean-Marc; Yao, Ignace; N’guessan, Edouard; Bohoussou, Eric; Guié, Privat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: In order to improve the quality of care for patients discharged in our department, since 1996 we have initiated monthly meetings called "common staffs", with the heads of the peripheral maternities who evacuate patients, during which we analyse reference indicators and the SONUs. The objective of this study was to describe the impact of the common staff on the indicators of the reference. Methods: We carried out a retrospective cross-sectional study on the balance sheets of the common staff over the 20 years of practice. Results: In 20 years, 132 meetings were organized, during which 24,337 files were analyzed. In 1996 the indicators of evacuations were at alarming levels: the time taken between the diagnosis and the decision to evacuate was long (more than 1 hour in 83.4%), 73% of the evacuation records were poorly informed, the majority evacuations were by non-medical vehicle (54.8%), pre-discharge management was incorrect in several patients (47%), and maternal and fetal lethality were high (5% and 10%, respectively). Over time, these indicators have improved and have had a favourable impact on maternal and fetal mortality rates, which have gradually decreased. At the same time, the results of the last three years of the evacuees coming from the maternities who do not participate in our staffs, shows that the indicators are still alarming, at levels where we were at the beginning of common staffs. Conclusions: The joint staff proved to be a good practice to promote in the Gynecology and Obstetrics Departments. It helped to improve the quality of care for referred patients.